2014
DOI: 10.1124/jpet.114.217968
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Prevents High-Fat Diet–Induced Obesity in C57BL/6 Mice by Suppressing the Sterol Regulatory Element-Binding Protein Pathway

Abstract: Sterol regulatory element-binding proteins (SREBPs) are major transcription factors regulating the expression of genes involved in biosynthesis of cholesterol, fatty acids, and triglycerides. We investigated the effect of the specific SREBP suppressor andrographolide, a natural compound isolated from Andrographis paniculata, on the regulation of SREBP signaling by use of Western blot, reporter gene assay, and quantitative real-time polymerase chain reaction analysis. In addition, the antiobesity effects of and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 42 publications
3
44
0
1
Order By: Relevance
“…Both results are in agreement with our observations and suggest that reduced HTC, also observed by Ding et al . 16 , and liver inflammation in ANDRO-treated mice fed with CDAA diet compared with vehicle-treated animals fed with the same diet may be related, at least in part, to modulation of hepatic inflammasome. Of note, since the CDAA diet feeding model is of more intense and long-term model of NASH, with all liver features of the disease compared to more ‘metabolic’ models such as high-fat diet fed mice or short-term nutritional models such as methionine-choline-deficient diet-induced NASH, we were able to also document an anti-fibrotic action of ANDRO in the setting of NASH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both results are in agreement with our observations and suggest that reduced HTC, also observed by Ding et al . 16 , and liver inflammation in ANDRO-treated mice fed with CDAA diet compared with vehicle-treated animals fed with the same diet may be related, at least in part, to modulation of hepatic inflammasome. Of note, since the CDAA diet feeding model is of more intense and long-term model of NASH, with all liver features of the disease compared to more ‘metabolic’ models such as high-fat diet fed mice or short-term nutritional models such as methionine-choline-deficient diet-induced NASH, we were able to also document an anti-fibrotic action of ANDRO in the setting of NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a recent report by Ding et al . 16 showed that ANDRO was effective in preventing fat accumulation in liver of high-fat diet fed mice through regulation of sterol regulatory element-binding proteins (SREBPs) target genes. However, these authors did not explore further the effects of ANDRO on either inflammation or fibrosis in their animals due to shortcomings of the experimental models used.…”
Section: Introductionmentioning
confidence: 99%
“…They are implicated in complicated pathogenic processes such as endoplasmic reticulum stress, inflammation and autophagy, and as a result, they contribute to obesity, dyslipidemia, diabetes mellitus, AS and NAFLD (20). AG regulated SREBP and other metabolism-associated genes in liver or brown adipose tissue, which may have directly contributed to the lower lipid levels and enhanced insulin sensitivity in mice with high fat diet (HFD)-induced obesity (21). Decrease of pathological lesions contain AS and NAFLD in ApoE knockout (ApoE -/-) mice with HFD can be controlled by regulating the lipid metabolism and inflammatory (22).…”
Section: Introductionmentioning
confidence: 99%
“…A s a l a b d a n e d i t e r p e n o i d i s o l a t e d f r o m Andrographispaniculata, andrographolide has been widely used in treatment of various human diseases including different types of cancers (7), obesity (8), oxidative damage (9), and so on. Andrographolide is also a safe and effective drug for treatment of various inflammatory diseases (10).…”
Section: Introductionmentioning
confidence: 99%